1999
DOI: 10.1016/s0002-9440(10)65245-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined Morphological and Interphase Fluorescence in Situ Hybridization Study in Multiple Myeloma of Chinese Patients

Abstract: To gain insight into the real incidence of the numeric chromosomal aberrations and the cell lineage involvement of the neoplastic process in multiple myeloma (MM) , we examined 18 Chinese MM patients by May-Grunwald-Giemsa (MGG) staining and fluorescence in situ hybridization using three DNA centromeric probes specific for chromosomes 3 , 7 , and 9. In this investigation , cytogenetic abnormalities were detected in plasma cells (PCs) , myeloid cells (MCs), and lymphoid cells (LCs) in all of the MM patients stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…A recent study has revealed that BMI-1 is a transcription repressor that targets the ink4a locus, which encodes the p16 protein and that BMI-1 cooperates with c-myc by repressing p16 and P19/ ARF. Of note, the p16 protein is often absent in myeloma cells (Ng et al, 1997). Though a promoter hypermethylation has been invoked, our data suggest that BMI-1 could contribute to p16 silencing in MM.…”
Section: Myc and Myc Partnersmentioning
confidence: 59%
“…A recent study has revealed that BMI-1 is a transcription repressor that targets the ink4a locus, which encodes the p16 protein and that BMI-1 cooperates with c-myc by repressing p16 and P19/ ARF. Of note, the p16 protein is often absent in myeloma cells (Ng et al, 1997). Though a promoter hypermethylation has been invoked, our data suggest that BMI-1 could contribute to p16 silencing in MM.…”
Section: Myc and Myc Partnersmentioning
confidence: 59%
“…Methylation of the 5'CpG island of p16 is another mechanism for inactivation of this gene, and several tumors have been reported to show this alteration Gonzalez-Zulueta et al, 1995a;Fueyo et al, 1996;Wong et al, 1997;Ng et al, 1997;Herman et al, 1997). In this report, methylation of p16 promoter was analysed in 15 tumor specimens from ten bladder cancer patients as well as seven squamous metaplasia specimens from two bladder cancer patients and ®ve cancer free patients.…”
Section: Discussionmentioning
confidence: 99%
“…These two genes are frequently deleted in several kinds of tumors (Kamb et al, 1994;Nobori et al, 1994;Cairns et al, 1995). De novo methylation of the 5'CpG island in the promoter of p16, which inhibits the expression of p16 but not p19 Gonzalgo et al, 1998), is another mechanism of the gene silencing, and has been reported to occur frequently in a variety of cancers Fueyo et al, 1996;Gonzalez-Zulueta et al, 1995a;Wong et al, 1997;Ng et al, 1997;Herman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recently various methods were developed for the combination of MGG staining with FISH at the single cell level such as the manual search for PC [27], the combined immunofluorescent PC detection and FISH [23, 24, 26]and the purification of PC with anti-CD138-coated magnetic beads [25, 28]. All these methods are time-consuming, may lead to loss of PC, and have limitations related to immunofluorescent PC detection, allowing only the analysis of BM samples with >30% of PC.…”
Section: Introductionmentioning
confidence: 99%